Understanding the Efficiency of Aluminum Coagulants Used in Dissolved Air Flotation (DAF) - Miranda, Ruben; Latour, Isabel; Blanco, Angeles (Frontiers in Chemistry, 2020)
This paper reports on the efficiency of five aluminum coagulants for the treatment of industrial process waters by dissolved air flotation (DAF). The coagulants studied were: alum, a polyaluminum chloride coagulant of high aluminum content and intermediate basicity (PAC-MB), another with intermediate aluminum content and high basicity (PAC-HB), a polyaluminum nitrate sulphate of intermediate aluminum content and basicity (PANS) and one hybrid coagulant formed by the combination of PANS and a mixture of polyamines (PANS-PA). The influence of Al speciation on contaminants removal and the main flocculation mechanisms involved have been analyzed. High removal of suspended solids together with significant removal of dissolved and colloidal material (COD and silica) were obtained, which is required for extended reuse of this process water. PAC-HB was the best for removing suspended solids and soluble silica, while PANS-PA obtained high turbidity and silica removal together with an intermediate soluble COD removal. Monomeric Al (Ala, Alm) was more efficient in removing suspended solids and soluble COD than polymeric or colloidal Al (Alc, Alu), but the latter was more efficient in removing soluble silica. Results demonstrated that the main flocculation mechanism varies with the aluminum dosage, being predominantly charge neutralization at low dosages and sweep flocculation at high dosages. The floc strength factor however, was very high and similar for all the coagulants and dosages tested (85-90%), as it was mainly determined by the behaviour of the pre-flocculated suspended solids present in wastewater. The reflocculation factor varied from 45-75% at the lowest dosages to almost zero at the highest dosages, confirming the transition from charge neutralization to sweep flocculation. The flocs formed by PANS-PA had lower strength than the others and it decreased with the dosage while its reflocculation factor was almost zero, even at low dosages. Due to the polyamines present in this coagulant, its flocculation mechanism is through both charge neutralization and patch formation, especially at low dosages, and sweep flocculation and interparticle bridge formation at high dosages.